The tsar's foreign faiths: toleration and the fate of religious freedom in Imperial Russia - Werth, Paul W. (Oxford studies in modern European history, 2014)
"The Russian Empire presented itself to its subjects and the world as an Orthodox state, a patron and defender of Eastern Christianity. Yet the tsarist regime also lauded itself for granting religious freedoms to its many heterodox subjects, making "religious toleration" a core attribute of the state's identity. The Tsar's Foreign Faiths show that the resulting tensions between the autocracy's commitments to Orthodoxy and its claims to toleration became a defining feature of the empire's religious order."--